Measuring dynamics of emotions evoked by the packaging colour of hamburgers(1) using Temporal Dominance of Emotions (TDE) - Merlo, Thais Cardoso (2019)
We would like to thank Jorge Cabrera for his help with designing the packaging. E. Saldaña received the support of the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica – CONCYTEC” from Peru (CIENCIACTIVA programme, PhD scholarship contract agreement No. 104-2016-FONDECYT). Thais C. Merlo thanks “Coordenação de Aperfeiçoamento de Pessoal de Nível Superior” (CAPES) for the scholarship. We would like to thank the valuable contributions of the two anonymous reviewers as they significantly improved the preliminary version of the present study.